2021
DOI: 10.1186/s13012-021-01093-4
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Incentivizing appropriate malaria case management in the private sector: a study protocol for two linked cluster randomized controlled trials to evaluate provider- and client-focused interventions in western Kenya and Lagos, Nigeria

Abstract: An amendment to this paper has been published and can be accessed via the original article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The study was reviewed and approved by CHAI's Scientific and Ethical Review Committee (SERC) on October 22 nd 2019; Duke University Institutional Review Board (Pro00104256) and the Health Research and Ethics Committee Secretariat (HREC) at the Lagos State University Teaching Hospital (LASUTH) (LREC/06/10/1304) in Lagos, Nigeria. The study is registered in ClinicalTrials.gov (NCT04428307) and the protocol and revisions to the original design were published in advance [9,10].…”
Section: Ethical Considerations and Trial Registrationmentioning
confidence: 99%
See 2 more Smart Citations
“…The study was reviewed and approved by CHAI's Scientific and Ethical Review Committee (SERC) on October 22 nd 2019; Duke University Institutional Review Board (Pro00104256) and the Health Research and Ethics Committee Secretariat (HREC) at the Lagos State University Teaching Hospital (LASUTH) (LREC/06/10/1304) in Lagos, Nigeria. The study is registered in ClinicalTrials.gov (NCT04428307) and the protocol and revisions to the original design were published in advance [9,10].…”
Section: Ethical Considerations and Trial Registrationmentioning
confidence: 99%
“…These results are pending publication elsewhere [8] . Full details of the study design were previously reported in Woolsey et al [9,10].…”
Section: Overall Study Designmentioning
confidence: 99%
See 1 more Smart Citation